COVID-19 Anxiety and Rumination in University Students in The COVID-19 Process - Binaz Bozkur; Mustafa Güler (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This study aims to determine the relationship between COVID-19 anxiety and rumination in university students and to examine the contributions of rumination in predicting COVID-19 anxiety. The research group of this study, which was conducted using the descriptive method and the relational scanning model, consisted of 417 students (86.1% female, 13.9% male) studying in different programs at Selçuk University. “COVID-19 Rumination Scale (C-19RS)”, “Coronavirus Anxiety Scale Short Form” and personal information form are data collection tools used in the study. Data collected for the research was analyzed via SPSS 25.00 package program. Correlation analysis was used to determine the relationships between COVID-19 anxiety and rumination scores of university students, while regression analysis was performed to determine the contribution of rumination scores in predicting COVID-19 anxiety scores. As a result of the research, there was a moderately significant positive correlation between the COVID-19 anxiety scores of university students and their rumination scores. Rumination scores of university students were found to be a significant predictor of COVID-19 anxiety scores, explaining 31% of the variance in their COVID-19 anxiety scores. The research findings were discussed in light of the literature